Immunoexpression of Androgen Receptor and Nine Markers of Maturation in the Testes of Adolescent Boys with Klinefelter Syndrome: Evidence for Degeneration of Germ Cells at the Onset of Meiosis - Wikström, Anne M.; Hoei-Hansen, Christina E.; Dunkel, Leo; Rajpert-De Meyts, Ewa (The journal of clinical endocrinology and metabolism, 2007)
Context: The pathogenesis and mechanisms behind the degeneration of the seminiferous tubules in testes of subjects with Klinefelter syndrome (KS) are yet unknown. Objective: The objective of this prospective clinical study was to characterize the testicular degeneration process during puberty in boys with KS by describing the immunoexpression of some developmentally regulated markers of testis maturation in relation to serum levels of reproductive hormones. Setting: This study was conducted at a university central hospital pediatric referral endocrinology outpatient clinic. Patients: Patients consisted of 14 boys with KS aged 10.1 to 14.0 yr. Main Outcome Measures: Main outcome measures were immunoexpression of germ cell differentiation markers (AP-2γ, CHK2, OCT-3/4, NY-ESO-1, MAGE-A4) and androgen action-related proteins [androgen receptor (AR), anti-Müllerian hormone (AMH), MIC2, inhibin B; α- and βB-subunits] in testicular biopsies of boys with KS in relation to serum reproductive hormone levels. Results: In boys with KS, gonocytes differentiated to the spermatogonium stage, but no spermatocytes were visible. Despite this, down-regulation of AMH expression in the Sertoli cells occurred concomitantly with decreasing serum AMH levels. Expression of inhibin α- and βB-subunits appeared in the biopsies even when circulating inhibin B levels were undetectable. In the boys with KS compared with age-matched controls, the proportion of Sertoli cell nuclei expressing AR was smaller and cytoplasmic staining of Sertoli cells was constantly present. Conclusions: We showed with several testis-specific markers in KS that gonocytes differentiate to spermatogonia and that the degeneration of the testes accelerates at the onset of puberty. Altered immunoexpression of AR indicates that a relative androgen deficiency, at least at the testicular level, develops in boys with KS during puberty.